Evaluation of Selected Internet Portals for Booking Accommodation by Polish Consumers: A Survey Study - Anna S. KOWALSKA; Anna OLSZAŃSKA; Dominika KOWALSKA; Klaudia GURKOWA; Joanna SZYMAŃSKA (Communications of International Proceedings, 2023)
The study aimed to identify which factors are essential when booking accommodation using online accommodation booking portals, as well as to examine how respondents evaluate the selected portals in terms of these factors. The survey was conducted in October 2022, with a group of 119 respondents. The assessment of individual portals was carried out using the Statistica 13.3 program, specifically the PROFIT analysis.  The study the Pearson's chi-squared test was used. For pairs of significantly dependent variables the strength of the relationship was also calculated using the V Cramer's test and its direction using the D'Sommer's test. The results show that Booking.com is the best-perceived portal for booking accommodation according to respondents. All the discussed features were rated the highest by respondents. The other three portals mentioned by respondents that they use significantly differed from the Booking.com portal.
Keywords: travel services; online accommodation booking portals; e-commerce; PROFT multidimensional analysis.